Realities and perspectives of Romanian beekeeping - Aurelian Buliga-Ṣtefănescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
This article presents an analysis of the beekeeping sector in Romania and its prospects. In order to carry out this research, data about the honey producers' associations, official statistical information, articles and specialized scientific treatises were processed. Romania is one of the most important honey producers in the European Union. It boasts about 40 thousand beekeepers, out of whom 23161 are registered in associations, totaling over 1.69 million bee families. Every year, over 25 thousand tons of honey are produced on average. From this point of view, the best year was 2015 when Romania ranked first in Europe, with a production of 30.1 thousand tons of honey. However, in terms of consumption, Romania is at the bottom of the ranking. Annually, a Romanian consumes only 550 grams of honey on average. In 2018 Romania exported honey worth 49.4 million (occupying the 14th position globally, with 2.2% weight) and imported honey worth 11.4 million (occupying the 27th position globally, with a weight of 0.5%).
Keywords: Q10; Q13; Q17; O13; 330; honey production; bee families; producers; beekeeping